Diagnostic Accuracy of Fluorescence Microlymphography for Detecting Limb Lymphedema. Issue 4 (April 2015) - Keo, H.H.; Husmann, M.; Groechenig, E.; Willenberg, T.; Gretener, S.B.
Abstract : Objectives: Fluorescence microlymphography (FML) is a minimally invasive technique for visualization of the cutaneous lymphatic network. The aim of the study was to assess the accuracy and safety of FML in patients with unilateral lymphedema. Methods: This was a cross sectional study. Patients with unilateral leg swelling were assessed and compared with the unaffected contralateral limb. FML was performed in all index legs and the contralateral leg by injecting 0.1 mL of fluorescein isothiocyanate (FITC)-labeled dextran intradermally in both limbs at the same level. The most prominent swelling of the affected limb was the anatomical reference. The spread of the dye in the lymphatic capillaries of the skin was measured in all dimensions by epiluminator intravital microscopy and the maximum dye spread value 10 min after injection was used for statistical analysis. The contralateral leg served as control. Test accuracy and receiver operator characteristic (ROC) analysis was performed to assess threshold values that best predict lymphedema. Results: Between March 2008 and February 2014 seventy patients with unilateral chronic leg swelling were clinically diagnosed with lymphedema. The median age was 45 (IQR 27–56) years. Of those, 46 (65.7%) were female and 71.4% had primary and 28.6% secondary lymphedema. Sensitivity, specificity, positive and negative likelihood ratio, and positive and negative predictive value were 94.3%, 78.6%, 4.40, 0.07, 81.5%, and 93.2% for the 12 mm cut off level and 91.4%, 85.7%, 6.40, 0.10, 86.5%, and 90.9% for the 14 mm cut off level, respectively. The area under the ROC curve was 0.89 (95% CI: 0.83–0.95). No major adverse events were observed. Conclusions: FML is an almost atraumatic and safe technique for detecting lymphedema in patients with leg swelling. In this series the greatest accuracy was observed at a cut off level of ≥14 mm maximum spread.